Developmental skills of 36-60-month-old children in Isfahan daycare centers in 2013 - Zohreh Ghazavi; Zahra Abdeyazdan; Elham Shiravi; Sedigheh Talakob (Wolters Kluwer Medknow Publications, 2015)
Background: Assessment of developmental skills is one of the most essential components of children's health evaluation. Since several pubertal disorders are caused by parental negligence in diagnosis, prevention, and treatment of childhood problems, failure to make a timely diagnosis of these problems could have adverse effects on the health of children in future. This study was conducted to determine the developmental skills of 36-60-month-old children in Isfahan. Materials and Methods: In this cross-sectional study, 196 children, aged 36-60 months, were recruited through random cluster sampling. "Ages and Stages" questionnaire was filled for each subject by their parents (father, mother, or both), and the frequency of developmental delay was determined based on cut-off points. The data were analyzed by descriptive statistics using SPSS 20.0. Results: About 52.6% of the children were male. Mean age of the children was 50.71 (SD = 8.16) months. The abnormal findings were in the five domains of communication (1.5%), gross motor (3.1%), fine motor (7.7%), problem solving (7.7%) and personal-social (2%). Conclusions: The results suggest that some of the children had scores below or equal to the cut-off points and needed more evaluation by a professional person. The domains in which the children had problems were fine motor, problem solving, and gross motor. Therefore, health staff should pay more attention to assessment of these domains and parents should be trained to develop their children's skills in these domains.